The Book of Nasa’ih Al-‘Ibad and Tanqih Al-Qaul by Shaykh :Nawawi Al-Banteni: A Comparative Study on The Method :Syarh Hadit - Kirin, Dr.Arwansyah; Mardhiah, Wan Ainaa; Siti Marpuah, Dr.Siti Marpuah; Husen Ismail, Dr.Faisal; Masruri, Dr.Muhammad; Rahman, Dr.Riki
Shaykh Nawawi al-Banteni is a famous scholar who has produced many scientific works in the archipelago. Among his works is the book Nasa'ih al-'Ibad which is exegesis from the book al¬Munabbahat 'Ala al-'Isti'dad Li Yaum al-Ma'ad by Ibn Hajar al-Asqalani and the book Tanqih al-Qaul which is exeges from the book Lubab al-Hadith by Jalal al-Din al-Suyuti. Both of these works are a reference in several pesantrens in Indonesia and are also widely taught in certain suraus, halakah and mosques. However, the in -depth study of the method of syarh the hadith of the book is rarely noticed by the users of the book. Therefore, it is important to explain the method of syarh hadith found in these two books in order to know its status and also to measure the extent of the author's knowledge in the knowledge of hadith. This study intends to explore the method of syarh hadith by Shaykh Nawawi in the book Nasa’ih al-‘Ibad and Tanqih al-Qaul. The purpose of this study is to analyze the method of syarh hadith used by Shaykh Nawawi and reveal the extent of his knowledge and status as a scholar of hadith through the books of Nasa'ih al-‘Ibad and Tanqih al-Qaul. The methodology of this study is qualitative through the method of content analysis by focusing on the books of Nasa’ih al¬‘Ibad and Tanqih al-Qaul. This study found that there are similarities and differences in the methodology of exegesis hadith in the books of Nasa’ih al-‘Ibad and Tanqih al-Qaul by Shaykh Nawawi al-Banteni. In addition, he also has good ability and knowledge in the knowledge of hadith.